2005
DOI: 10.1074/jbc.m507553200
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Poly(ADP-ribose) Polymerase-1 by p300/CREB-binding Protein Regulates Coactivation of NF-κB-dependent Transcription

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) and nuclear factor B (NF-B) have both been demonstrated to play a pathophysiological role in a number of inflammatory disorders. We recently presented evidence that PARP-1 can act as a promoter-specific coactivator of NF-B in vivo independent of its enzymatic activity. PARP-1 directly interacts with p300 and both subunits of NF-B (p65 and p50) and synergistically coactivates NF-B-dependent transcription. Here we show that PARP-1 is acetylated in vivo at specific lysine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
252
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(272 citation statements)
references
References 56 publications
15
252
0
1
Order By: Relevance
“…As a regulator of gene expression, PARP-1 seems to play a critical role in both these processes. Thus, PARP-1 contributes to NF-B activation in the inflammatory response, provoking CREB binding protein recruitment independent of poly[ADP]-ribosylation (Hassa et al, 2005). In contrast, PARP-1 enzymatic activity is need for the recruitment of coactivators to Elk-1 and Hes-1 during neuronal activation and neurogenesis, respectively (Ju et al, 2004;Cohen-Armon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As a regulator of gene expression, PARP-1 seems to play a critical role in both these processes. Thus, PARP-1 contributes to NF-B activation in the inflammatory response, provoking CREB binding protein recruitment independent of poly[ADP]-ribosylation (Hassa et al, 2005). In contrast, PARP-1 enzymatic activity is need for the recruitment of coactivators to Elk-1 and Hes-1 during neuronal activation and neurogenesis, respectively (Ju et al, 2004;Cohen-Armon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a transient assay, over expression of PARP1 was found to repress the transcription of genes containing the M-CAT sites, again suggesting that PARP1 has a dual role in gene expression, activation followed by repression, depending upon the degree of PARP activation [107]. Recent studies have also shown that PARP1 is a target of acetylation and decatylation by p300/pCAF and class-I HDACs, respectively, but not by the class-II HDACs [142]. Acetylation of PARP1 has been shown to stabilize its interaction with other partner proteins, e.g., NFkB and TEF1 (unpublished observation), leading to activation of their target genes, whereas the opposite is true for deacetylation of PARP1 by class-I HDACs [142].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 98%
“…Recent studies have also shown that PARP1 is a target of acetylation and decatylation by p300/pCAF and class-I HDACs, respectively, but not by the class-II HDACs [142]. Acetylation of PARP1 has been shown to stabilize its interaction with other partner proteins, e.g., NFkB and TEF1 (unpublished observation), leading to activation of their target genes, whereas the opposite is true for deacetylation of PARP1 by class-I HDACs [142]. In the context of the effect of TSA on αMHC gene induction, it is therefore possible that some effects of the class-I HDAC inhibition by TSA could be mediated by acetylation of PARP1, resulting in de-repression of the transcriptional activity of the TEF1/PARP1 complex.…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 99%
“…PARP-1 has been reported to be a co-activator of NF-kB in many inflammatory disorders (Pétrilli et al, 2004;Zheng et al, 2004). Indeed, it has been proposed that acetylation of PARP by p300/CREBbinding protein plays an essential regulatory role in NFkB-dependent transcription gene expression (Hassa et al, 2005). A series of evidences have shown that NF-kB binds to an NF-kB sequence in the VEGF-C promoter (Chilov et al, 1997;Zhang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%